Sweat gland morphology and physiology in diabetes, neuropathy, and nephropathy: a review - Singaram, Sudha; Ramakrishnan, Kalpana; Selvam, Jayashree; Senthil, Mallika; Narayanamurthy, Vigneswaran (Taylor and Francis Ltd., 2022)
Context: Sweat glands (SGs) play a vital role in thermal regulation. The function and structure are altered during the different pathological conditions.